Apuntes sobre la concepción benjaminiana del lenguaje - Cuesta, Micaela (Nómadas. Critical Journal of Social and Juridical Sciences, 2008)
On this article we propose to retrace the tracks left by Benjamin in his conception of language. We consider that this conception can be retraced not only in his early article entitled On the language in general and on the language of the men, but also in those that tell us about The task of the translator, On the mimética Faculty or The education of the resemblance. The questions that accompany us in this journey can be enounced as follows: ¿In what or whom was Benjamin thinking when he develops his conception of language? ¿What does Benjamin understand when he speaks of language? ¿Is language an exclusive and excluding human property? ¿What relations are susceptible to be established between language and translation? ¿What is the place on these developments of the suggestive article On the mimética Faculty? ¿Is it possible to derive from the benjaminian theory of language a conception of experience, or even more, one of history?